A method validation and analysis of lead content in lipstick products sold in e-commerce using atomic absorption spectrophotometer (AAS) - Dian Prasasti; Divanda Liling Sasanti (Farmasains : Jurnal Farmasi dan Ilmu Kesehatan, 2021)
Lipstick is the most widely cosmetic that used to beautify the appearance of the face. Lipstick that safe to use has an amount of lead metal less than 20 ppm. This study aims to ensure that the analytical method used has been validated, to determine the metal content of lead in lipsticks that sold in e-commerce, to determine the average metal content of lead using an Atomic Absorption Spectrophotometer (AAS) and to determine the safety of the lipstick. The methods used to validation are determine linearity, accuracy, precision, LoD, and LoQ. Samples were obtained from e-commerce with criteria that had price less than IDR 17,500, had sales history at least 10,000 units and had shipments from within the country. Sample preparation was carried out by wet digestion method, then analyzed qualitatively by tube test and analyzed quantitatively by measuring its absorption using AAS. The results obtained from this study are the linearity of validation parameter is 0.9959, the percent accuracy is entirely in the range 80-110%, the percent precision is less than 11% and the LoD and LoQ numbers are 0.630 ppm and 1.908 ppm. The average levels of lead contained in lipsticks that sold in e-commerce for brands A to F are 33.285±0.918 ppm; 33.576±0.918 ppm; 35.029±0.918 ppm; 38.372±1.836 ppm; 39.390±0.918 ppm; and 32.994±0.918 ppm. Lipstick brands A, B, C, D, E, and F contain more than 20 ppm lead metal so they are not safe for daily use.